Teaching programming: A mind map based methodology to improve learning outcomes - Gul, Shahla; Asif, Muhammad; Ahmad, Waqar; Ahmad, Uzair (2017 International Conference on Information and Communication Technologies (ICICT), 2017)
Computer programming requires many skills. Among these skills, problem solving skills are one of the core skills required to learn programming. Different strategies and methods have developed to improve students' problem solving skills for better programming learning but the problem still exists. In this experimental study, we investigated the effectiveness of Mind Maps as a brainstorming and conceptualization tool for helping students to analyze problems and plan its programming solutions. Moreover, the implications of employing mind maps with both Text and Blocks-based programming environments are presented. The results of this study show that mind map-based methodology worked well with both text and blocks-based programming languages for improving learning outcomes of students.